Pemberian Edukasi Kesehatan Reproduksi Dan Pemberian Tablet Tambah Darah Sebagai Upaya Pencegahan Stunting Pada Remaja - Christiana, Indah; Yulifah Salistia Budi (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
One of the causes of stunting is iron deficiency. Iron is essential in optimizing the First 1,000 Days of Life (HPK), including preventing stunting. Adolescents who marry at a young age have risks, especially for babies, such as low birth weight (LBW), prematurity, asphyxia, and stunting. Therefore, young women need to ensure their physical preparedness, which includes maintaining a nutritious diet and preventing anemia. Additionally, they should know about toddlers' growth and development and readiness to face stunting. This community service activity aims to increase knowledge about reproductive health and provide iron tablets, especially to teenagers in Rusunawa, Klatak Village, Banyuwangi. The implementation method involves educating about reproductive health, checking hemoglobin (Hb) levels, and administering iron tablets. The activity results showed that before being given education about reproductive health, the average knowledge of teenagers was 31, and there was an increase in knowledge of 52 points after being given education, and none of the teenagers in the flats suffered from anemia. At the end of the activity, distribute ten blood supplement tablets taken once a week.